ROLE OF RANDOMIZED TRIALS IN PHARMACOEPIDEMIOLOGY - T. L. Galankin; A. S. Kolbin (IRBIS LLC, 2015)
Abstract: pharmacoepidemiology has recently evolved into a self-dependent post-marketing disciplinefrom clinical pharmacology, borrowing its methodology and analyticaltools from epidemiology. The article describes the goals of pharmacoepidemiology and provides introduction to randomized designs in post-marketing drug research by the example of large simple trials.